2009
DOI: 10.1063/1.3133222
|View full text |Cite
|
Sign up to set email alerts
|

Thickness scalability of large volume cadmium zinc telluride high resolution radiation detectors

Abstract: Articles you may be interested inInvestigating the effect of characteristic x-rays in cadmium zinc telluride detectors under breast computerized tomography operating conditions Investigation of the internal electric field in cadmium zinc telluride detectors using the Pockels effect and the analysis of charge transients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Even though the THM technique emerged as a good method to grow large crystals of CZT and CdTe, it has a major disadvantage that other growth methods may not have, that is it introduces an additional source of Te inclusions in the ingots because of the microscopically irregular melt-solid interfaces during growth, which can trap the Te-rich CZT solution forming inclusions [21,22]. Post-growth annealing is required to mitigate this problem [11,12]. Therefore, it has become clear to us that in our work on optimizing the THM technique we must reduce the number of Te inclusions formed at these interfaces.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Even though the THM technique emerged as a good method to grow large crystals of CZT and CdTe, it has a major disadvantage that other growth methods may not have, that is it introduces an additional source of Te inclusions in the ingots because of the microscopically irregular melt-solid interfaces during growth, which can trap the Te-rich CZT solution forming inclusions [21,22]. Post-growth annealing is required to mitigate this problem [11,12]. Therefore, it has become clear to us that in our work on optimizing the THM technique we must reduce the number of Te inclusions formed at these interfaces.…”
Section: Introductionmentioning
confidence: 98%
“…Hence, for the last two decades, researchers have explored various techniques to grow large CZT crystals free of these flaws. The growth techniques used include high-pressure Bridgman, conventional Bridgman, gradient freeze, and the traveling heater method (THM) [6][7][8][9][10][11][12][13][14]. Among them, THM has proven to be the most promising in yielding many large, uniform single-crystalline CZT and CdTe ingots [11,14].…”
Section: Introductionmentioning
confidence: 98%
“…CZT has been proposed as having the capability to create revolutionary advances in medical imaging [13], but for the small size and high cost of CZT crystals. Recently, however, reports [14][15][16] have shown that largesized and cheaper CZT crystals with even better signal output can be grown in commercial quantity using the ''Travelling Heater Method''.…”
Section: Introductionmentioning
confidence: 98%
“…In 1994, Mokri et al [14] demonstrated the THM growth of CZT with good compositional homogeneity. In the recent past traveling heater method (THM) has proven to be the most cost effective technique for mass production of good quality CdTe and CZT with higher yield [15][16][17]. Other than the compositional homogeneity of the grown ingots, THM offers many other advantages compared to melt growth techniques due to its low temperature growth process.…”
Section: Introductionmentioning
confidence: 98%